2013
DOI: 10.1187/cbe.13-02-0043
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Mentors Training Underrepresented Undergraduates in the Research Laboratory

Abstract: The goal of this research was to better understand the experiences and perspectives of mentors in a program designed to increase the number of American Indian students garnering PhDs. Challenges and benefits associated with mentoring undergraduates were identified through semistructured interviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 23 publications
4
80
0
2
Order By: Relevance
“…Indeed, implementation of a recent adaptation of Entering Mentoring developed for the mentors of early career clinical and translational researchers significantly increased mentors’ self-reported mentor competency ratings and also significantly increased their mentees’ rating of mentor effectiveness (Pfund et al, 2013; Pfund et al, 2014). Importantly, Entering Mentoring includes diversity and inclusion considerations which is especially important given that White research mentors working with underrepresented racial/minority undergraduates may view their mentoring relationships as unaffected by cultural diversity (Prunuske, Wilson, Walls & Clark, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, implementation of a recent adaptation of Entering Mentoring developed for the mentors of early career clinical and translational researchers significantly increased mentors’ self-reported mentor competency ratings and also significantly increased their mentees’ rating of mentor effectiveness (Pfund et al, 2013; Pfund et al, 2014). Importantly, Entering Mentoring includes diversity and inclusion considerations which is especially important given that White research mentors working with underrepresented racial/minority undergraduates may view their mentoring relationships as unaffected by cultural diversity (Prunuske, Wilson, Walls & Clark, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mentors need to provide professional socialization and emotional support so that students can integrate their ideas about their scientific identity with the setbacks and confusions they encounter in their interactions with the members of the lab. One study shows that mentors can challenge students to become aware of the tension between their own cultural norms and those of the scientific community (35). Other investigations found that students who feel supported by faculty are more likely to go to graduate school (22), that frequency of meetings with faculty mentors correlates with student confidence to perform science practices or pursue a research career (36), and that students who lack interactions with mentors and fail to get direction for research projects are likely to change career plans away from science (37).…”
Section: Mentoring Participantsmentioning
confidence: 98%
“…Byars-Winston et al [25] found that URM students were more likely than their predominantly White mentors to endorse that cultural diversity matters should be addressed in the research mentoring relationship [37]. Prunuske et al [40] found that mentors of URM mentees tended to espouse colorblind attitudes and the notion that cultural diversity is irrelevant to the research mentoring relationship [40]. Does it matter to the effectiveness of the mentoring relationship if the mentor and mentee are aligned in their views on addressing cultural diversity issues?…”
Section: The Need To Study Mentoring Relationshipsmentioning
confidence: 99%